SEGMENTATION AND MARKETING STRATEGY OF USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) PRODUCTS IN THE NEW NORMAL ERA - Irene Nathalia Setiawan; C. Tri Widiastuti; Wahyu Puspitasari (Universitas Muhammadiyah Semarang, 2023)
UMKM are one of the pillars and have a significant role for the economy in Indonesia. In the era of the Covid-19 pandemic, UMKM are facing various kinds of problems. This condition is a challenge in itself in seeking UMKM to be able to survive and rise in the era of the Covid-19. The purpose of this study was to analyze the impact of the Covid-19 on tempe businessman in the Sendangguwo, Semarang. Qualitative method through in-depth interviews with key informants, the entrepreneurs in the Sendangguwo, Semarang. The results of the study concluded that the tempe product segmentation is very attached to the people in Indonesia, especially in Java so that all levels of society can be classified as able to accept the product for consumption both in terms of price and product quality. The marketing strategy for tempe products can be carried out in various levels of society according to the target market segment and good price competition.